2016
DOI: 10.1016/j.scitotenv.2016.01.077
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of PM 2.5 from two tunnels with different vehicular fleet characteristics

Abstract: • Composition profiles of PM 2.5 were obtained in smaller city, Yantai.• Characteristics of PM 2.5 were changed by emission standards and fuel policy.• Source profiles of PM 2.5 for gasoline vehicles and diesel vehicles were given.• The diesel vehicles play a major role in PM 2.5 emissions in Yantai. The chemical compositions of PM 2.5 including OC, EC, water soluble ions, elements, and organic components such as polycyclic aromatic hydrocarbons (PAHs), hopanes, and steranes, emitted in Wuzushan (WZS) and Kuix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 48 publications
10
43
3
2
Order By: Relevance
“…Therefore, the results obtained from the real-world conditions (on-road tests and tunnels) are different from those obtained in a laboratory. For organic matter, the proportion of PAHs, hopanes, and steranes to PM are consistent with the results of Schauer et al (1999) and Cui et al (2016). In this study, the most abundant n-alkane was C20, as measured by Schauer et al (1999), and pyrene was the most abundant PAH, as reported by Cui et al (2016).…”
Section: Average Source Profile Of Pm For Truckssupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, the results obtained from the real-world conditions (on-road tests and tunnels) are different from those obtained in a laboratory. For organic matter, the proportion of PAHs, hopanes, and steranes to PM are consistent with the results of Schauer et al (1999) and Cui et al (2016). In this study, the most abundant n-alkane was C20, as measured by Schauer et al (1999), and pyrene was the most abundant PAH, as reported by Cui et al (2016).…”
Section: Average Source Profile Of Pm For Truckssupporting
confidence: 92%
“…In comparison, the total carbon emissions in this study are lower than those in previous studies, whereas the WSIs and elements fractions are higher (Alves et al, 2015a;Cui et al, 2016;Schauer et al, 1999;Wu et al, 2016). Several factors have influenced these differing results such as fuel quality, driving condition, engine parameters (fuel injection timing, compression ratio, and fuel injector design), and experimental methods (Sarvi et al, 2008a(Sarvi et al, , b, 2009Sarvi and Zevenhoven, 2010).…”
Section: Average Source Profile Of Pm For Truckscontrasting
confidence: 72%
See 3 more Smart Citations